Evaluation of selected soil nutrient availability and pH in oil palm plantations: Assessing the impact of ganoderma disease in Chini, Pahang, Malaysia - Nurin Maisarah Rosham Kadiman; Nur Shuhada Muhamad Tajudin; Noor Syaheera Mohd Yunus; Siti Nurhusna Johari; Nurul Mayzaitul Azwa Binti Jamaludin (International Islamic University Malaysia, 2024)
Oil palm management involves the usage of fertilizer to satisfy the oil palm's needs as a heavy nutrient feeder. Over time, fertilization and irrigation practices could have attracted pathogenic microorganisms and affect the soil nutrient availability. The present study has been conducted to evaluate the current soil status in the area of oil palm plantation in Chini, Pahang by assessing the soil pH, total organic carbon (TOC), and selected soil nutrient availabilities; potassium (K), magnesium (Mg), calcium (Ca), zinc (Zn), copper (Cu), and aluminium (Al). Sampling were conducted based on the oil palm according to severity of the Ganoderma disease incidence evaluated by the plantation authorities. The distribution of nutrient in the soil samples were analyzed using atomic absorption spectroscopy (AAS). From the results, the soil pH were mostly found as acidic, ranging from 3.6 to 6.2. The mean concentrations of the K, Ca, Mg were observed the highest in soils from category A, the healthiest category with least incidents of Ganoderma, and the mean concentrations of micronutrients (Zn, Cu, Mn, Al) varied between all soil categories. This initial study is crucial as a foundational study that sets the stage for understanding soil nutrients availability and pH status with the occurrence of Ganoderma species.